Benign Mucinous Tumor of Ovary with a Sarcoma-Like Mural Nodule: A Case Report - Sailabala Garikaparthi; Renuka Inuganti Venkata; Krishna Bharathi Yarlagadda; Annapurna Parvatala (Case Reports in Oncological Medicine)
Sarcoma-like mural nodules occur predominantly in middle-aged women. Distinction of these lesions from true sarcomatous nodules and foci of anaplastic carcinoma is important because of the worse prognosis of these tumors in comparison with the favorable behavior of sarcoma-like mural nodules. In this report we describe the case of a 35-year-old woman with a mucinous ovarian tumor having a mural nodule in the wall.